Evaluación in vitro de extractos vegetales obtenidos manualmente en el laboratorio de diagnóstico veterinario de la Universidad Nacional de Loja para el control de garrapatas en bovinos - Yaguana Jaramillo, Karla Lizeth (2016)
In the present work investigation it was done the in vitro evaluation of plant extracts obtained by hand in the national loja university in the veterinary diagnostic laboratory to control ticks in cattle, specific Objectives: To evaluate in vitro effect of plant extracts as tickcide in cattle, to determine the ticks’ taxonomy, to determine the time of extract effect used in different evolutive stages, twenty ticks were used in each petri dish with three replicates and a control group for each extract, the variables studied were: effectiveness of mortality, larval mortality and nymphal, inhibition of oviposition inhibition of larval hatching, and experimental design it was completely randomized. Four species were evaluated; Mamey (American Mammea), Neem (Azadirachta indica), garlic (Allium sativum) and Mandarin (Citrus reticulata). The best results were obtained with mamey (American Mammea), using seeds aqueous solution the adult ticks mortality 83%, with cooked leaves 67%, 100% larval mortality, nymphal mortality 100% , the oviposition inhibition 100%, effective inhibition of larval eclosion 100%, Neem seeds (Azadirachta indica), has excellent results in adult ticks mortality 82% with cooked leaves 75% , larval mortality 100%, nymphal mortality 100% , the inhibition oviposition 100%, the inhibition of larval eclosion 100%, Macerated Garlic (Allium sativum) has efficacy in adult ticks mortality 78%, larval mortality 68% nymphal mortality 100%, the oviposition inhibition 100% the inhibition of larval eclosion 100%, tangerine (Citrus reticulata), has significant results in adult ticks mortality 77%, larval mortality 100% . Nymphal mortality 100%, oviposition 71.7%, the inhibition of larval eclosion 100%.